Heterotopic pregnancy after use of ovulation induction: report of a case - Herrera, César (2015)
A rare case of heterotopic pregnancy after use of ovulation-inducing communicates refers its presentation, diagnosis method, the applied therapy, pathologic examination, its evolution, a literature review of the subject and some comments relevant.